Aquaculture Research and Development as an Entry-Point and Contributor to Natural Resources and Coastal Management - Haws, Maria; Crawford, Brian; Portella, Maria Celia [UNESP]; Ellis, Simon; Jiddawi, Narriman; Mmochi, Aviti; Gaxiola-Camacho, Eladio; Rodriguez-Dominguez, Guillermo; Rodriguez, Gustavo; Francis, Julius; Rivas Leclair, Carlos; Saborio Coze, Agnes; et al. (Taylor & Francis Inc, 2010)
Recent, fervent international dialogue concerning the existence and magnitude of impacts associated with aquaculture has had both positive and negative outcomes. Aquaculture stakeholders have become sensitized to requirements for improved environmental management of aquaculture. on the other hand, in some cases aquaculture development has been negatively affected by some of the unwarranted and unproved allegations to the detriment of the stakeholders most in need of aquaculture development (i.e., resource users, particularly the poor, who are dependent on natural resources). These resource users are targeted by, and directly influence biodiversity and conservation agendas; hence the need to understand how to gain their active participation. This discussion focuses on examples of how aquaculture research and development can be a useful tool or strategy for resource management initiatives and provide tangible positive including increased stakeholder participation and cooperation, offering alternatives to resource extraction and use in otherwise difficult or intransigent resource management conflicts.
Keywords: Amazonian fishes; aquaculture; community-based management; mariculture; Mexico; Micronesia; Nicaragua; stock enhancement